PARTICULAR ISSUES OF ADAPTATION OF NATIONAL LEGISLATION IN THE FIELD OF ATMOSPHERIC AIR PROTECTION TO THE REQUIREMENTS OF THE EUROPEAN UNION - Gordienko, Artur (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to characterise certain issues of adaptation of national legislation in the field of atmospheric air protection to the requirements of the European Union. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain high-quality results. Therefore, the following research methods were used to solve the tasks: analysis; systematic method; analytical method, etc. Results: in accordance with the provisions of the current regulatory legal acts in the field of atmospheric air protection, the main legal mechanisms of state regulation of atmospheric air protection are regulation and standardisation in the field of atmospheric air protection. Discussion: regulation of the location of facilities and sources of air pollution, conducting state environmental and other examinations of facilities that have a significant impact on the environment and human health, the permitting procedure for state authorisation of activities that may be accompanied by emissions into the environment, establishment of sanitary protection zones around enterprises that are a source of impact on the environment and people. The author concludes that an important place in the protection of atmospheric air is occupied by technical standards. In many cases, environmental legislation contains references to technical regulations, sanitary norms, environmental quality standards, maximum permissible concentrations of pollutants in natural objects, etc…